SOLUCIÓN LOCAL DE UNA ECUACIÓN DE KIRCHHOFF NO LINEAL VISCOELÁSTICA CON TÉRMINO DISIPATIVO - Quispe Méndez, Teófanes (2007)
In this work, we study the existence and uniqueness of the local solutions to themixed problem for a type of viscoelastic nonlinear Kirchhoff 's equation with dissipativeterm.